2013
DOI: 10.2991/ccis-13.2013.64
|View full text |Cite
|
Sign up to set email alerts
|

Design and Implementation of Data Encryption in Cloud based on HDFS

Abstract: Abstract-As an open-source distributed programming framework, Hadoop has gradually become popular in industry recently. Its distributed file system (HDFS) enables storing large data with advantages of high fault tolerance and throughput. However, the fact that the current HDFS does not support intra-cloud data encryption yet makes data privacy becomes a key security issue. This paper presents ahybrid encryption method based on HDFS. We adopt symmetric encryption to encrypt and decrypt file blocks at datanodes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…The experiments indicated that HDFS performed best when big data is partitioned into smaller file sizes. It can be inferred from Figures 3, 4, and 5 that our securing algorithm outperforms its counterparts in [32] and [46] for response time, delay time, and throughput.…”
Section: ) Secured Data Transmission Throughputmentioning
confidence: 85%
See 4 more Smart Citations
“…The experiments indicated that HDFS performed best when big data is partitioned into smaller file sizes. It can be inferred from Figures 3, 4, and 5 that our securing algorithm outperforms its counterparts in [32] and [46] for response time, delay time, and throughput.…”
Section: ) Secured Data Transmission Throughputmentioning
confidence: 85%
“…User authentication at the sender and the receiver clouds are carried out by integrating a user private key with a public key. Our security experimental results are compared with non-secured Hadoop baseline [4] and the secured methods proposed in [46] and [32].…”
Section: ) Big Data Transmission Response Timementioning
confidence: 99%
See 3 more Smart Citations